ANALISA PENGGUNAAN TERAPI ANTIBIOTIK PADA PASIEN BEDAH DI Rumah Sakit ROYAL PRIMA MARELAN - Nurul Apla Wizaya Syahputri; Ermi Girsang; Ali Napiah Nasution (Postgraduate, University of Mataram, 2023)
The use of antibiotics in surgical patients aims to reduce Surgical Site Infection (SSI) so that it can reduce the number of patient admissions to hospital. Fully used antibiotics in patientâ€™s cancontributes to the spread of antibiotic resistance, so it is necessary to evaluate the use of antibiotics in hospitals.Quantitative and qualitative assessment of antibiotic use is an important metric in evaluating rational antibiotic prescribing and controlling drug resistance. This study aims to evaluate the use of antibiotics in surgical patients at Royal Prima Marelan Hospital based on assessing the quantity and quality of use. This research is a retrospective study using an observational-analytic design using a quantitative and qualitative approach with secondary data referring to the medical records of 200 surgical patients who received antibiotic therapy and were treated at the Royal Prima Marelan Hospital in the period June - November 2022. Quantitative analysis was carried out using the method ATC/DDD and qualitative analysis using Gyssens criteria. Correlation analysis uses the contingency coefficient statistical test. The results of the quantity of antibiotic use show that the total DDD/100 patient-days value is 77.6 and the quality of antibiotic use using the Gyssens criteria is appropriate/rational, with the most widely used antibiotic being ceftriaxone and the majority of patients' length of stay being â‰¤ 7 days. This research shows that age (p=0.761), gender (p=0.920), and quality of antibiotic use (p=0.610) do not correlate with length of stay in surgical patients at Royal Prima Marelan Hospital for the period June - November 2022.